The effect of educational digital games in seventh grade students' achievement in English and retention of information (Journal of Hama University, 2025)
This study aimed at exploring the effect of educational digital games in seventh grade students' achievement in English in Damascus state schools and measuring its effect in students’ retention of information. A quasi- experimental approach was undertaken in this study. The total number of participants was 60 in a state school in Damascus during the academic year 2023-2024. The sample consisted of two groups: the control group (30) students, and the experimental group (30) students. The instruments of the study were an achievement test and interactive digital games. The SPSS statistical program was used to analyze the study data and the hypotheses were tested at the level of significance (α= 0.05).The findings of the study showed that educational digital games had positive effect on students' English learning achievement. Students who were taught English by using games improved their achievement more than those who were taught by using the traditional method of teaching. In addition, Students of the experimental group retained information better than those in the control one. A number of suggestions were proposed for further researches to examine the effect of the educational digital games on other subjects and educational stages.
Keywords: Effect, Educational Digital Games, Seventh Grade Students, Achievement, Retention